Effect of Date of Sowing on Yield and Yield Attributes of Different Wheat Varieties under Conventional Tillage in Sub-Humid Condition of Chitwan District of Nepal - Marasini, Dinesh; Marahatta, Santosh; Dhungana, Surya Mani; Acharya, Ramesh (International Journal of Applied Sciences and Biotechnology, 2016)
A field experiment was conducted at the Agronomy farm of Institute of Agriculture and Animal Science (IAAS), Rampur during winter season of 2014/2015 to find out the response of wheat varieties under different sowing dates. There was 9 treatments consisting three date of sowing (November 14, November29 and December 14) in main plot and three varieties namely Tillotama, Danfe and Vijay in sub-plot and were arranged in split plot design with three replications. The grain yield was significantly higher (3.09 tha-1) at November 14 whereas highest straw yield was recorded for November 29 sown wheat (5.61 t ha-1). Effective tiller (414) and number of grain per spike (34.34) were highest for November 29 sown wheat. The late sown wheat had more sterile floret (42.65%) while early sown wheat had highest thousand grain weight (51.23 g). Danfe had highest straw yield (5.87 t/ha). Effective tiller/m2 (419) and sterility percentage (43.35%) of Danfe was highest. Number of grains per spike (37.89) of Tillotama was highest and thousand grain weight (57.09 g) of Bijay was found highest. The grain yield of Bijay (3.30tha-1) was highest when it was sown at November 29. Int J Appl Sci Biotechnol, Vol 4(1): 27-31